PELUANG DAN ANCAMAN TERHADAP KEBIJAKAN DALAM NEGERI INDONESIA - Suhud Alynudin Suhud Alynudin (NIAGARA Scientific Journal, 2018)
President Jokowi on several occasions expressed his view that Indonesia needs to be part of the Trans Pacific Partnership, a scheme free trade between pacific countries which aims to accelerate liberalization of international trade. International Cooperation always as opportunities and threats to the domestic policies of a country including the Trans Pacific Partnership (TPP).